Educational Quality Assurance and National Educational Standards: Results and Expectations - Phumphongkhochasorn, Phumphakhawat; Somruay Pindon, Phrapanyarattanakorn; Damnoen, Somchai; Vaddhano , Phra Thanat; Panglaor, Natthakorn (Asia Pacific Journal of Religions and Cultures, 2022)
Nowadays, it is widely accepted that quality and educational standards are important for all parties involved. In the provision of education must be aware and proceed to achieve results in accordance with the educational standards set. The educational quality assurance system is an important mechanism to help improve the quality and education standards effectively. National Education Act 1999 and as amended to (No. 3) 2010 Sort 6 Section 48 specify that the jurisdiction and the educational institution have established the internal quality assurance system of the school and consider the internal quality assurance as part of the educational administration process that must be continuously implemented. School prepares an annual report for submission to related departments in order to improve the quality according to educational standards and support external quality assessments afterward. Ministry of Interior has announced early childhood education standards, Basic education standards and practice guidelines for educational quality assurance for internal quality assurance of schools under the local administrative organization. They set standards and issues for consideration to be less, more compact, truly reflect quality, emphasize on real assessment, not complicated, create standardized assessment system, reduce the storage burden, and reduce the preparation of documents used for evaluations. This article presents an international standard for education management to be an appropriate guideline.